EDUCATORS AND COLLEGE STUDENTS ABILITY IN ENVIRONMENTAL CARE ATTITUDE - Nelly Yusra; Sakilah; Rian Vebrianto; Yovita; Umar Faruq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimeds to describe the lecturers’ and college students’ ability in environmental care attitude in Pekanbaru. This research is a descriptive qualitative research which was designed through a survey method. The samples were selected using purposive sampling, obtaining 100 people consisting of 16 teachers, 7 lecturers, and 77 students in Pekanbaru. Data were collected through questionnaires and further analyzed based on the Miles and Huberman model including data reduction, data presentation, and conclusion drawing/verification. The results showed that the average score of the environmental care attitude of the lecturers was 90% with a good category. Meanwhile, the average score of the environmental care attitude of the college students was 89.5% in the good category. Thus, it can be concluded that this indicates that educators and students have a good environmental care attitude.